Pseudoxanthoma elasticum-like papillary dermal elastolysis in non-exposed skin, - Nuria Setó-Torrent; Maribel Iglesias-Sancho; Jorge Arandes-Marcocci; María Teresa Fernández-Figueras (Anais Brasileiros de Dermatologia, 2020)
Abstract Pseudoxanthoma elasticum-like papillary dermal elastolysis is an acquired elastic tissue disorder clinically similar to pseudoxanthoma elasticum in the absence of systemic involvement. Histopathologically, special staining of elastic fibers demonstrates a total or partial band-like loss of elastic fibers in the papillary dermis. Although ultraviolet radiation seems to be one of the main etiological factors in this entity, we report a case of pseudoxanthoma elasticum-like papillary dermal elastolysis on the neck of a woman who wore hijab.